A comprehensive overview on the micro- and nano-technological encapsulation advances for enhancing the chemical stability and bioavailability of carotenoids. Issue 1 (2nd January 2018) - Soukoulis, Christos; Bohn, Torsten
ABSTRACT: Carotenoids are lipophilic secondary plant compounds, and their consumption within fruits and vegetables has been positively correlated with a decreased risk of developing several chronic diseases. However, their bioavailability is often compromised due to incomplete release from the food matrix, poor solubility and potential degradation during digestion. In addition, carotenoids in food products are prone to oxidative degradation, not only lowering the nutritional value of the product but also triggering other quality deteriorative changes, such as formation of lipid pro-oxidants (free radicals), development of discolorations or off-flavor defects. Encapsulation refers to a physicochemical process, aiming to entrap an active substance in structurally engineered micro- or nano-systems, in order to develop an effective thermodynamical and physical barrier against deteriorative environmental conditions, such as water vapor, oxygen, light, enzymes or pH. In this context, encapsulation of carotenoids has shown to be a very effective strategy to improve their chemical stability under common processing conditions including storage. In addition, encapsulation may also enhance bioavailability (via influencing bioaccessibility and absorption) of lipophilic bioactives, via modulating their release kinetics from the carrier system, solubility and interfacial properties. In the present paper, it is aimed to present the state of the art of carotenoid microencapsulation in order to enhance storability and bioavailability alike.